Belief in Unsubstantiated Claims about LGBTQ+ and Discriminatory Behaviour of Slovak LGBTQ+ and Heterosexually-identified Adolescent Boys and Girls Towards Sexual and Gender Minorities - Daniel Lenghart; Michal Čerešník; Martin Dolejš; Nikoleta Kontová (InterAlia)
The study aimed to map the homonegative, binegative, and transnegative behaviour rates in Slovak LGBTQ+ boys and girls and heterosexual boys and girls. The study involved an analysis of unsubstantiated LGBTQ+ claims and myths, which significantly increase the rate of discriminatory behaviour in adolescence. Research tools used include the Homonegativity, Binegativity, and Transnegativity Scale and the Unsubstantiated Claims and Myths about LGBTQ+ Scale. The research involved 209 adolescents from the Slovak Republic: 77 heterosexually-identified boys, 25 LGBTQ+-identified boys, 71 heterosexually-identified girls, and 36 LGBTQ+-identified girls. Results show that the heterosexually-identified adolescent population manifests higher homonegative, binegative, and transnegative behaviour rates. These differences manifest at both cognitive and emotional levels, as well as at a behavioural level. We identified the rate of belief in unsubstantiated LGBTQ+ statements and myths. Heterosexually-identified adolescents are more likely to be influenced by such statements than LGBTQ+-identified adolescents.